2017
DOI: 10.3989/mc.2017.04716
|View full text |Cite
|
Sign up to set email alerts
|

Ageing evolution of foamed warm mix asphalt combined with reclaimed asphalt pavement

Abstract: ABSTRACT:The combination of high rates of reclaimed asphalt pavement (RAP) and warm mix asphalt (WMA) technologies is still ambiguous in terms of durability. With the aim of clarifying this issue, a study comparing a hot mix asphalt with a WMA prepared using the foaming process technology. Both mixes contain 50% of RAP and are submitted to a laboratory ageing procedure. The long term related performance of the mixtures is compared by means of complex modulus and fatigue testing. Penetration and ring and ball t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Due to the aforementioned factors, increasing popularity of warm-mix asphalt techniques is seen, which created scientific interest in the properties and long-term durability of foamed mixtures. These properties of warm-mix asphalt mixtures, among other factors, are highly dependent on the composition, temperature, and aging history of bituminous binders [ 26 , 27 , 28 ]. Studies conducted during the construction of test sections using various warm-mix techniques [ 29 ] have shown that their utilization in many cases severely impacts the high-temperature grade of the asphalt binders extracted from the paved mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the aforementioned factors, increasing popularity of warm-mix asphalt techniques is seen, which created scientific interest in the properties and long-term durability of foamed mixtures. These properties of warm-mix asphalt mixtures, among other factors, are highly dependent on the composition, temperature, and aging history of bituminous binders [ 26 , 27 , 28 ]. Studies conducted during the construction of test sections using various warm-mix techniques [ 29 ] have shown that their utilization in many cases severely impacts the high-temperature grade of the asphalt binders extracted from the paved mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches are not easily linked to the effects of aging at the molecular level and a correlation between the microstructure and the physical response lacks a unique definition (2,5,13,(28)(29)(30). Despite this, rheological indicators (e.g., viscosity, linear and non-linear viscoelastic functions) have been used to substantiate results from compositional test methods to provide clear insights on the changes in bitumen microstructure and their effects on performance (3,(31)(32)(33)(34). In the case of PMBs, the rheological analysis becomes even more complicated since the response is affected by non-Newtonian effects, strain dependency, thixotropy, and uncertainties about the applicability of the time-temperature superposition principle (TTSP) (37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…Specifications regarding these can be found in many countries (Dinis-Almeida et al, 2012). Other processes are newer techniques that produce warm and half-warm recycled mixtures about which much research is being conducted to verify the properties of the resulting mixture (Romier et al, 2006;Gaudefroy et al, 2007;Dinis-Almeida and Lopes, 2015;Lopes et al, 2015;Lu et al, 2016;Mallick et al, 2008;Punith et al, 2012;Van de Ven et al, 2007;Pérez-Martínez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%